Confirmatory Analysis And AHP In Measuring Community Welfare Indicators - Nurdelila, Nurdelila; Pathuansyah, Yusuf (Jurnal Ekonomi, 2024)
The objective of this study was to measure the level of community welfare using a Confirmatory analysis and the Analytic Hierarchy Process (AHP). The research focuses on key welfare indicators, including material well-being, safety, and self-actualization. The study was conducted in the regions of Padangsidimpuan Utara and Padangsidimpuan Selatan with a sample of 165 households. Data were collected through questionnaires and interviews and analyzed using the confirmatory factor analysis (CFA) method to validate the welfare indicators. The results indicate that the main factors contributing to community welfare are housing, health, income, and savings. Housing emerged as the most influential factor, followed by health and income. The AHP method further emphasized that the quality of housing materials, particularly flooring, plays a significant role in determining welfare. These findings suggest that targeted policies addressing housing quality and healthcare can significantly improve community welfare.